Analyzing Strategies of Coca-Cola to Achieve Environmental Protection and Corporate Profit - Wang, Cunting (Transactions on Economics, Business and Management Research, 2024)
Coca-Cola unveiled its "World Without Waste" sustainable packaging initiative in 2018. In 2022, the corporation executed this plan with a series of eco-friendly initiatives in the Chinese market. This study aims to examine how Coca-Cola reconciles environmental conservation with company profitability in the execution of its “World Without Waste” sustainable packaging initiative. This research analyzes data on plastic packaging content and theoretical concepts related to brand image and brand loyalty. It delineates three major factors: the execution of a circular economy strategy, the strategy for recycled packaging materials, and packaging promotional activities. Furthermore, it presents three recommendations: utilizing lighter plastic packaging, integrating designs inspired by traditional Chinese culture, and employing internet marketing strategies. This study contributes to the notion of corporate social responsibility (CSR) by demonstrating how firms can bolster their brand image and promote consumer loyalty through environmental protection activities, thereby facilitating long-term sustainable development.